Perkawinan Adat Suku Dayak Meratus Di Kalimantan Selatan - Fathul Achmadi Abby; Ifrani Ifrani; Muhammad Topan (Jurnal Penegakan Hukum Indonesia, 2021)
This research is aimto study, the customary marriage law of indigenous people of the Dayak Kotabaru Regency, South Kalimantan.Second, the marriage law based on the Dayak Customs of the Kotabaru Regency of South Kalimantan comparedto studies and teachings of the Customary Law? The research method used in this study is the socio-legal legal research. Theresearchis not only limited to examining the law as a series of norms or statutory rules related to customary law of Dayak, but also examining the living law. Such legal research can also be called a sociological juridical research method. The results ofthe research show that first, there are two concepts of marriage relations in the Dayak customary tribe, first there is marriage based on the sacred bond of marriage (legal marriage) and secondly is 'palas', which is a relationship that appears without a legalmarriage bond and can even be considered adultery. Second, the legal norms of Dayak customary marriage are based on the principles of customary law, namely the principle of harmony, the principle of decency and the principle of linearity.